Cultivares de feijão-de-corda, vigna sinensis (L.) savi, resistentes à meloidoginose - Lemos, José William Veras (1978)
Cowpea crop, Vigna sinensis (L.) Savi, is consider ably affected by root-knot nematodes, Meloidogyne spp., in Northeast of Brazil [...]